? Interaction Between Saprophytic and Pathogenic Fungi (Biological Sciences - PJSIR, 2022)
interminglinggrowth with Alternaria solani and Aureobasidumpullulans with Cladosporium cladosporioides. Therefore, thesearc least inhibitory. Highest inhibition zone was observed withA. terre us for both the pathogens. The maximum inhibition in.growth of these two test fungi was observed when grown withAspergillus terreus and Trichoderma viridae. This may be inpart due to production of some antifungal substances or maybe due to spatial problem. A. terreus has been reported toproduce antibiotics such as gcodin, terricin and terric acid [6].These antibiotics might be providing inhibitions in the growthof the pathogenic fungi.